2011
DOI: 10.1177/039463201102400210
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating the Clinical and Immunomodulatory Effects of an Orally Administered Extract ofDendrobium Huoshanensein Children with Moderate to Severe Recalcitrant Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a common inflammatory skin disorder for which few safe and effective systemic treatments are available. To test the clinical and immunomodulatory effects of a crude polysaccharide fraction isolated from Dendrobium huoshanense for the treatment of AD, we conducted a pilot, uncontrolled case series study. Twenty-seven patients aged 4-18 years (mean±SD, 10.82±4.4) with AD that had not responded to topical therapy were treated with polysaccharide derived from D. huoshanense for 4 weeks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Increasing the turnover of bile salts has a beneficial effect on low-density lipoprotein cholesterol levels, which is an important risk factor for the development of atherosclerosis and playa relevant role in aging (24-29). Elevated plasma LDL cholesterol and triglyceride levels and reduced HDL cholesterol levels are associated with an increased risk of developing atheroma and shorter life (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Increasing the turnover of bile salts has a beneficial effect on low-density lipoprotein cholesterol levels, which is an important risk factor for the development of atherosclerosis and playa relevant role in aging (24-29). Elevated plasma LDL cholesterol and triglyceride levels and reduced HDL cholesterol levels are associated with an increased risk of developing atheroma and shorter life (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Several species of Dendrobium exerted neuroprotective activities, but their evaluation on modern targets should be undertaken in the future. Their immunomodulatory activities are promising and interesting clinical studies on patients with Sjögren syndrome or atopic dermatitis have been reported [ 104 , 108 ]. In light of recent discoveries about the connections between immunity and diseases developed in the elderly, this lead would continue to be explored and more clinical studies would be realized to confirm in vitro and in vivo investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide from D. huoshanense reduced the levels of some cytokines associated with atopic dermatitis and had beneficial effects on symptoms. No serious adverse effects occurred when it was administered orally for 4 weeks [ 104 ].…”
Section: Immunomodulatory Propertiesmentioning
confidence: 99%
“…The diverse chemical characteristics of the polysaccharides from Dendrobium may be correlated with their health benefits. More than 70 Dendrobium species had been found in China; however, only three of them, namely D. officinale , D. huoshanense and D. moniliforme , were most valuable and have different efficacy . D. officinale and D. moniliforme are also the two most commonly used species in China.…”
Section: Introductionmentioning
confidence: 99%
“…More than 70 Dendrobium species had been found in China; however, only three of them, namely D. officinale, D. huoshanense and D. moniliforme, were most valuable and have different efficacy. 6,7 D. officinale and D. moniliforme are also the two most commonly used species in China. These valuable Dendrobium species have commonly been employed as different forms of dietary supplements in various herbal commodity markets in China.…”
Section: Introductionmentioning
confidence: 99%